2022
DOI: 10.1371/journal.pone.0265577
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing personality characteristics define clinically relevant subgroups of alcohol use disorder

Abstract: Aims Higher levels of externalizing characteristics, i.e. impulsivity, novelty seeking and aggression, could contribute to the development, progression and severity of alcohol use disorder (AUD). The present study aims to explore whether these externalizing characteristics together have a potential group-forming role in AUD using latent profile analysis (LPA). Methods Externalizing characteristics of 102 AUD patients were analyzed using LPA to explore the group-forming role of externalizing symptoms; groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Still, exploration or novelty-seeking is an essential aspect of behavior and has been well-documented, for example, in the preference for a novel object over a familiar object (Ennaceur and Delacour 1988 ). Novelty-seeking has been implicated as a predictive variable for animal drug-taking tendencies (O’Connor et al 2021 ) and connected to clinical substance abuse populations (Kovács et al 2022 ). Observations in nNOS-ko animals, such as frequent crossings and increased time in the center zone of the open field as well as increased time in the open arms of the elevated plus maze, could be interpreted as a form of exploratory behavior (Weitzdoerfer et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, exploration or novelty-seeking is an essential aspect of behavior and has been well-documented, for example, in the preference for a novel object over a familiar object (Ennaceur and Delacour 1988 ). Novelty-seeking has been implicated as a predictive variable for animal drug-taking tendencies (O’Connor et al 2021 ) and connected to clinical substance abuse populations (Kovács et al 2022 ). Observations in nNOS-ko animals, such as frequent crossings and increased time in the center zone of the open field as well as increased time in the open arms of the elevated plus maze, could be interpreted as a form of exploratory behavior (Weitzdoerfer et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drinking is associated with increases in physical aggression (Matuszka et al, 2017), and aggressive behavior is associated with greater alcohol consumption, heavy-drinking occasions, and alcohol-related/alcohol-involved aggression in adolescents (Tremblay & Ewart, 2005; White et al, 1993). Additionally, a latent class analysis demonstrated that individuals with an alcohol use disorder (AUD) can be characterized into two groups, those high in externalizing behavior, including aggression, and those low in externalizing behavior (Kovács et al, 2022), further suggesting an overlap between aggression and alcohol use behavior. However, it should be noted that there may be differential relations between alcohol use and verbal and physical aggression, as some studies have shown that binge-drinking and more extreme levels of alcohol consumption are more strongly associated with physical aggression compared to verbal aggression (Kraus et al, 2015; Wells et al, 2000).…”
mentioning
confidence: 99%